2022
DOI: 10.1186/s12889-022-12664-5
|View full text |Cite
|
Sign up to set email alerts
|

The differences of Slovenian and Italian daily practices experienced in the first wave of covid-19 pandemic

Abstract: Background The COVID-19 pandemic situation with the lockdown of public life caused serious changes in people's everyday practices. The study evaluates the differences between Slovenia and Italy in health-related everyday practices induced by the restrictive measures during first wave of the COVID-19 pandemic. Methods The cross-sectional cohort study examined changes through an online survey conducted in nine European countries from April 15–28, 202… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In a study conducted in Turkey, physical activity levels of adolescents decreased by 70.2% with the pandemic (Umac & Aydin, 2021). Similar results were obtained in Italy, Slovenia, Portugal, and Spain, with significant decreases in physical activity level compared to pre-pandemic (Branquinho et al, 2020;Orgiles et al, 2020;Pišot et al, 2022). During this period, increases were observed in food consumption, sleep duration and social media addiction.…”
Section: Introductionsupporting
confidence: 73%
“…In a study conducted in Turkey, physical activity levels of adolescents decreased by 70.2% with the pandemic (Umac & Aydin, 2021). Similar results were obtained in Italy, Slovenia, Portugal, and Spain, with significant decreases in physical activity level compared to pre-pandemic (Branquinho et al, 2020;Orgiles et al, 2020;Pišot et al, 2022). During this period, increases were observed in food consumption, sleep duration and social media addiction.…”
Section: Introductionsupporting
confidence: 73%
“…The COVID-19 pandemic has had a substantial impact on our original family models and relationships 22,23 . This is primarily due to the panic caused by the pandemic and the fear of being infected.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the number of partnered sexual activities also decreased 27 . When the pandemic began to isolate people at home, it offered them more contact time, which helped them to re-establish intimacy and improve their sexuality 23 . A study investigated the impact of the Wenchuan earthquake on women's reproductive health and found that after the earthquake, the frequency of sexual intercourse, sexual life satisfaction, and desire for children decreased 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In March 2020, the World Health Organization declared coronavirus disease 2019 (COVID-19) a pandemic (1). The first case of COVID-19 in Slovenia was reported on 04/ 03/2020 (2). By 20/10/2022, more than 620 million confirmed cases had been reported worldwide, with more than 5.5 million deaths (3).…”
Section: Introductionmentioning
confidence: 99%